Integrative taxonomy and a new species description in the sturtevanti subgroup of the Drosophila saltans group (Diptera: Drosophilidae) - Madi-Ravazzi, Lilian; Segala, Luís Fernando; Roman, Bruna Emilia; Alevi, Kaio Cesar Chaboli; Prediger, Carolina; Yassin, Amir; Hua-Van, Aurélie; Miller, Wolfgang J. (Zootaxa, 2021)
Although the biological concept of species is well established in animals, sometimes the decision about the specific status of a new species is difficult and hence requires support of an integrative analysis of several character sets. To date, the species Drosophila sturtevanti, D. magalhaesi, D. milleri and D. dacunhai, belonging to the sturtevanti subgroup of the Neotropical saltans species group, are identified mainly by the aedeagus morphology, but also present some differences in spot coloration and patterning of the female sixth tergite and in the shape and size of the spermathecae, parallel to a pattern of reproductive isolation. In the present study, we describe a novel saltans group species from French Guiana belonging to the sturtevanti subgroup. Our species designation is based on an integrative approach covering (i) aedeagi and spermathecae morphology by scanning electron microscopy, (ii) analysis of female sixth-tergite color, (iii) morphometrical analysis of aedeagi and wings, (iv) analysis of partial sequence of the COI, COII and ND4 mitochondrial genes as well as (v) intercrosses for analysis of reproductive isolation. The comparative analysis of the results on these markers with those of D. sturtevanti, D. milleri and D. dacunhai supports that this line belongs to a new species of the sturtevanti subgroup that we name Drosophila lehrmanae sp. nov. in honor of Prof. Lee Ehrman´s 85th birthday.